An Automatic Turn Signal System In Four Wheelers - et. al., K.Akila, B.Sabitha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper aims at developing the new automatic technology in the field of Automobile. Not pre- warning of the vehicle’s lane departure is the precursor to crashes. Especially during the driver’s idleness and wrongly turning on the turn signals ON and OFF during the lane change. Hence the idea proposed is about indicating the turn-lights automatically during the lane change, which helps in the reduction of accidents. Photo frames from the camera are captured and processed for lane detection and tracking the position of the vehicle between the lane that helps the controller which hold an algorithm to put the turn signal to left or right. As future possibilities, this field of work can be used in self-driving cars.